Incidence of early-onset glaucoma after infant cataract extraction with and without intraocular lens implantation. Issue 9 (7th May 2009) - Wong, I B Y; Sukthankar, V D; Cortina-Borja, M; Nischal, K K
Abstract : Aims: To determine the incidence of glaucoma, with onset within 1 year after the date of cataract surgery (early onset) performed in the first year of life, with or without intraocular lens (IOL) implantation. Methods: A retrospective review of a single surgeon's cohort from 1999 to 2006. Glaucoma onset risk, comparison of aphakic/pseudophakic eyes and IOL type were analysed together with microcornea, persistent fetal vasculature (PFV) and age ⩽4 weeks at surgery. Results: Ninety-eight eyes (62 patients; mean age 2.88 months) were included with 61 eyes (36 patients) aphakic (57 planned and four failed implantations), and 37 eyes (26 patients) pseudophakic. At a mean follow-up of 2.51 years, 15.3% (12.2% within 1 year) of all eyes, 9.8% of eyes (6.6% within 1 year) in the planned aphakic group, all four eyes with failed implantation and 13.5% of the pseudophakic eyes (10.8% within 1 year) developed glaucoma. Glaucoma incidence stratified by absence or presence of IOL showed no statistically significant difference, but eyes in the rigid polymethylmethacrylate group had an increased glaucoma risk compared with the Acrysof group (p = 0.002). Microcornea, PFV and age ⩽4 weeks at surgery were not significant predictors of early-onset glaucoma. Conclusions: In this single surgeon study of infant cataract surgery only, age ⩽4 weeks at surgery was not a predictor of early-onset glaucoma. The rate of aphakic and pseudophakic early-onset glaucoma was not found to be statistically different, but we found a statistically different rate of glaucoma between the two IOL types which needs further evaluation, given that this is a retrospective review. Excessive surgical trauma influences incidence of glaucoma.